(untitled) (Indian Journal of Animal Production and Management, 2024)
The aim of the study was to find out the effect of pre-partum habituation training on post-partum stress levels, milking behavior and production performance of primiparous Sahiwal cattle heifers. For this study, 10 advanced pregnant Sahiwal heifers were allotted to two groups of 5 heifers each. The T1 group was exposed to the environment of milking parlour and given training for milking for a period of 15 days before calving. There was significant (P<0.05) decline in mean plasma cortisol levels (from 16.11 to 5.61 ng/ml), milking temperament scores (from 2.67 to 1.40), ease of handling scores (from 2.40 to 1.13) and frequency of defecation during pre-partum period after one week of training in T1 heifers. During post-partum period, mean milking temperament score, ease of handling score, plasma cortisol concentrations after exposure to training protocol and amount of residual milk were significantly (P<0.05) lower in T1 than those in T0 heifer cows. Average normal daily milk yield over 7 weeks was significantly (P<0.05) higher (4.25 vs. 3.68 kg) in T1 than T0 cows whereas the total daily milk yield did not vary significantly between the two groups of cows. It was concluded that in-parlour habituation training and handling of advance pregnant Sahiwal heifers before calving for two weeks helped in reducing stress, improving milking behavior and lead to efficient milk ejection and higher milk yield during early lactation.